SARS-CoV-2 and ORF3a: Nonsynonymous Mutations, Functional Domains, and Viral Pathogenesis - Elio Issa (American Society for Microbiology, 2020)
ABSTRACT The effect of the rapid accumulation of nonsynonymous mutations on the pathogenesis of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is not yet known. The 3a protein is unique to SARS-CoV and is essential for disease pathogenesis. Our study aimed at determining the nonsynonymous mutations in the 3a protein in SARS-CoV-2 and determining and characterizing the protein’s structure and spatial orientation in comparison to those of 3a in SARS-CoV. A total of 51 different nonsynonymous amino acid substitutions were detected in the 3a proteins among 2,782 SARS-CoV-2 strains. We observed microclonality within the ORF3a gene tree defined by nonsynonymous mutations separating the isolates into distinct subpopulations. We detected and identified six functional domains (I to VI) in the SARS-CoV-2 3a protein. The functional domains were linked to virulence, infectivity, ion channel formation, and virus release. Our study showed the importance of conserved functional domains across the species barrier and revealed the possible role of the 3a protein in the viral life cycle. Observations reported in this study merit experimental confirmation. IMPORTANCE At the surge of the coronavirus disease 2019 (COVID-19) pandemic, we detected and identified six functional domains (I to VI) in the SARS-CoV-2 3a protein. Our analysis showed that the functional domains were linked to virulence, infectivity, ion channel formation, and virus release in SARS-CoV-2 3a. Our study also revealed the functional importance of conserved domains across the species barrier. Observations reported in this study merit experimental confirmation.